2018
DOI: 10.1111/ggi.13555
|View full text |Cite
|
Sign up to set email alerts
|

Association of dynapenia, obesity and chronic diseases with all‐cause mortality of community‐dwelling older adults: A path analysis

Abstract: Aim The objective of the present study was to evaluate the effect of dynapenia, central obesity and the presence of chronic diseases in 8‐year mortality of community‐dwelling older adults. Methods Participants comprised 610 older adults, aged ≥65 years at baseline, who participated in the “Frailty in Brazilian Older People” study carried out in 2008. Baseline data, such as weight, height, waist circumference, muscle strength, sex, self‐reported diseases and physical activity, were assessed. Vital status in 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
1
1
0
3
Order By: Relevance
“…There are strong consistencies that the two factors (SB and muscle strength) independently have mortality risk. 26 , 42 , 43 Nevertheless, the results of the present study confirm that this relationship, when high sedentary behavior and low muscle strength are combined concomitantly, increases the risk of mortality by more than 2 times. This result persisted even after adjusting for the individual's level of physical activity.…”
Section: Discussionsupporting
confidence: 73%
“…There are strong consistencies that the two factors (SB and muscle strength) independently have mortality risk. 26 , 42 , 43 Nevertheless, the results of the present study confirm that this relationship, when high sedentary behavior and low muscle strength are combined concomitantly, increases the risk of mortality by more than 2 times. This result persisted even after adjusting for the individual's level of physical activity.…”
Section: Discussionsupporting
confidence: 73%
“…It has been shown that dynapenia had a direct effect on increased mortality in 610 subjects aged 65 years or older [16]. In addition, a 10-year follow-up study involving 5310 older adults showed that the coexistence of anemia and dynapenia increased the mortality risk in both males and females [17].…”
Section: Discussionmentioning
confidence: 99%
“…Esta surge por meio de adaptações neuromusculares de origem fisiológica e, devido a influências do aumento de adiposidade corporal, são capazes de gerar infiltrações de gordura nos músculos (VOLAKLIS;HALLE;MEISINGER, 2015). Também observa-se que as alterações hormonais e de neurônios durante o envelhecimento, podem levar à diminuição das fibras musculares e à baixa atividade de mitocôndrias (KOMATSU et al,2018).…”
Section: Definição E Etiologia De Obesidade Dinapênicaunclassified